The impact of community/nutrition gardens as a strategy for coping with drought and climate change : the case of rural farmers in Bikita District Masvingo Zimbabwe - Terblanche, S.E. (Stephanus Esaias), 1940- (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2015.